Karya Tari â€œSebuah Catatan Harianâ€: Seni sebagai Media Pembelajaran bagi Anak-anak Tuna Rungu - Jonet Sri Kuncoro (Institut Seni Indonesia Surakarta, 2009)
This work try to become a reflection, that we are not alone in this world. In this globalization era where communications expand at full speed, thereâ€™s still the human being which